Penerapan Arsitektur Tropis Pada Perancangan Pusat Pelatihan Dan Pendidikan Bulutangkis Berstandar Internasional Di Tangerang Selatan - Ichsanul Ichsan Akbar; Anggraeni Dyah Sulistiowati (MAESTRO, 2019)
Application of Tropical Architecture to the Design of an International Standard Badminton Training and Education Center in South Tangerang is designed with the aim of providing a place or place for teenagers to be able to channel their talents to badminton with education and training in accordance with international standards. which will later produce talented young athletes who are able to compete on the world stage. This Badminton Education and Training has facilities that are so complete in accordance with the BWf International Standard, in terms of training that provides training places that are in accordance with international standards. Like the badminton rug that complies with the BWF standard used in International Tournaments, there are also other facilities such as educational facilities that are used as complementary facilities of badminton technique training, participant dormitories, places of worship, multipurpose rooms, dining rooms, clinics and international standard fields. The building design used for International standard Badminton Education and Training uses the concept of tropical architecture, the use of tropical architectural concepts is expected to be able to help the training well and can maximize multiple openings, to utilize natural lighting and lighting so that it can use sunlight on daytime. Keywords: Badminton Training Center, International Standard, South Tangerang, Tropical Architecture